2011
DOI: 10.1016/j.jpor.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of premolars restored with inlay and onlay ceramic restorations and luted with two different agents

Abstract: Within the limitations of this study, the cements tested had different mechanical properties, while cuspid coverage did not result in improved fracture resistance of the restored teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 33 publications
1
52
1
8
Order By: Relevance
“…Therefore, biomechanical tests that simulate the oral environment by reproduction of the chewing forces, temperature and humidity of the oral cavity are important in evaluating the performance of new materials (8). Fatigue testing meets these requirements and is used for testing dental materials like composite resins and ceramics (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The fatigue test simulates the clinical situation better than static compression test (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, biomechanical tests that simulate the oral environment by reproduction of the chewing forces, temperature and humidity of the oral cavity are important in evaluating the performance of new materials (8). Fatigue testing meets these requirements and is used for testing dental materials like composite resins and ceramics (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The fatigue test simulates the clinical situation better than static compression test (11).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports have shown that materials that exhibit high initial resistance do not always have high resistance to fatigue (5,6). Therefore, it seems appropriate that the strength of teeth restored with dental materials should be measured using a dynamic mechanical test rather than static tests (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…İlk geliştirilen dental seramiklerin düşük kırılma dirençleri nedeni ile posterior bölgede kullanımları kısıtlı kalmıştır. Zamanla yüksek dirençli seramiklerin ve porselen yüzeyinin asitlenerek rezin simanlar ile diş yüzeyine adeziv bağlantının geliştirilmesi ile seramik restorasyonların posterior bölgede kullanımı yaygınlaşmıştır [5][6][7][8] . Seramik inleyler Class I veya II restorasyonlar için estetik bir alternatif sunarlar.…”
Section: öZetunclassified
“…İnleylerin Avantaj ve Dezavantajları Dişin doğal morfolojisini restore etmesi, aşın-maya dirençli olması, biyouyumlu olması, polimerizasyon büzülmesinin siman film tabakası ile sınırlı kalması, uzun ömürlü ve estetik olması seramik inleylerin avantajlarıdır 6,13 . Seramiğin termal ekspansiyon katsayısı dişe benzer olduğundan hacimsel büzülme kompozit restorasyonlara göre daha az olmaktadır.…”
Section: Seramikunclassified
See 1 more Smart Citation